Lipids Fortified Nano Phytopharmaceuticals: A Breakthrough Approach in Delivering Bio-actives for Improved Therapeutic Efficacy - Shah, Sunny; Chauhan, Harshida; Madhu, Hardik; Mori, Dhaval; Soniwala, Moinuddin; Singh, Sudarshan; Prajapati, Bhupendra (Pharmaceutical Nanotechnology, 2025)
Phytopharmaceuticals, derived from natural sources, manifest tremendous potential for therapeutic applications. Nevertheless, effective delivery of these bio-actives presents significant challenges. A breakthrough in fortifying phytopharmaceuticals within phosphatidylcholine is a promising remedy to overcome solubility, permeability, and other related drawbacks. This intrinsic lipid, which is obtained from both natural and synthetic sources, confers numerous benefits, encompassing heightened solubility, augmented bioavailability, and enhanced stability. The conjugation of phytopharmaceuticals with phosphatidylcholine enables improved dermal permeation, absorption, targeted distribution, and the possibility of synergistic results, eventually improving therapeutic efficacy. Additionally, the use of phytopharmaceuticals enriched with phosphatidylcholine presents a promising route for overcoming the limitations imposed by conventional delivery techniques, encouraging more effective treatments. The review provides a thorough analysis of phosphatidylcholine-incorporated phytopharmaceuticals as nanomedicine with variables that significantly affect their therapeutic efficacy. Moreover, the review elaborates on how phosphatidylcholine improves solubility, permeability, and tissue distribution and boosts the potential of phytopharmaceuticals. Further, the review underscores the significance of nano-formulation strategies, analytical methodologies, and forthcoming prospects to propel this field forward. Furthermore, the review emphasizes the potential inherent in this innovative approach while highlighting the importance of additional research endeavors and collaborative initiatives to unlock the therapeutic benefits of phosphatidylcholine-fortified phytopharmaceuticals, enhancing patient well-being.
Keywords: phytopharmaceuticals